History of doping in world baseball/Historia del dopaje en el beisbol mundial - Victor Manuel Cabrera oliva; Pablo Castillo Díaz (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: baseball has been constantly under the threat of doping, and currently there are criteria issued by some experts that suggest the possibility that many successes achieved by famous baseball players who nowadays appear as the main big stars of this sport in the ballroom fame, have been related to the consumption of prohibited substances. Objective: the objective of this study was to explore the data published in the specialized world bibliography that reveal how doping, as well as other forms of fraud, have affected baseball in both the major and minor categories. Materials and methods: this bibliographic review work is carried out as a suggestion from baseball fans and the sports press interested in knowing how the problem of doping and the use of prohibited substances has influenced this sport since its origins. Results: Currently, doping control tests are carried out on amateur and professional players in the sport's leagues around the world. The tests, measures and sanctions that are applied conform to the prohibitions and standards issued by the World Anti-Doping Agency and the World Anti-Doping Code. The substances used most frequently have been anabolic steroids, stimulants, Growth Hormone and narcotics. Conclusions: once the competitive stage is over and with the passage to retirement, many baseball players begin to consume tobacco, alcohol and other drugs that significantly affect their health and quality of life.